Grid integration techniques of wind power plants - Zheng, Qingyu. (2011)
Wind energy is one of the most important and reliable sources of renewable energy used worldwide in recent years. The wind energy is converted into electricity using wind turbines. The main concentration of this report is on grid connected wind turbines. The electrical power produced by the wind turbines cannot be fed into the grid directly. It is because the power from the grid system and its quality has an influence on wind turbines performance, lifetime and safety. On the other hand, the quality and the reliability of wind turbine power will influence the quality, stability and reliability of the power from grid. Therefore, the controlling of the electrical power plays an important role for integration of wind power into the grid systems.